Towards a better understanding of management development in South Africa - P. Human; Linda Human (South African Journal of Business Management, 1989)
In this article, an attempt is made to provide a better understanding of management development in South Africa by the development of a theoretical framework within which the process of management development can be situated. It is argued that management development can be understood by using a framework of domination, which provides a useful conceptual model within which the basic dynamics of management development can be placed. This framework describes the structural positioning of the principal actors, the relationship between them, and the possible world-views which may arise from these positions. The problem of management development in South Africa is discussed in terms of this framework and practical solutions elicited.In hierdie artikel word 'n teoretiese raamwerk vir bestuursontwikkeling in Suid-Afrika voorgestel. 'n Beter begrip van bestuursontwikkeling kan moontlik verkry word deur die begrip van dominansie teoreties sentraal te plaas. Die raamwerk beskryf die strukturele posisies van die primere akteurs, die relasies tussen hulle en die moontlike wereldbeskouinge wat verbandhoudend is met verskillende posisies. Die probleme van bestuursontwikkeling in Suid-Afrika word bespreek in terme van die teoretiese raamwerk en praktiese oplossings word voorgestel.
Keywords: 650